The “voice colours”: expressing emotions through th e singing voice timbre - Pereira, Ana Leonor (2008)
Expression of emotions in singing is connected to a code with several parameters such as tempo, vibrato, rhythm, pitch, amplitude and timbre. The aim of this study is to understand how timbre expresses the performer’s emotions. Twelve professional singers were recorded while singing pieces of music with specific emotional content – Sadness, Joy, Anger and Fear – and a vocalise (Neutral). The data consisted of 432 vowels extracted from the perceptually accepted singing recordings judge by seven singing students. The results showed that formant frequencies changes are dependent on the emotions: Anger and Joy show higher formant frequency than Sadness and Fear. This investigation showed, also, that formants have specific functions: vowel discrimination is dependent on F2 and F1, individual discrimination is done by F4, F3 and F5, and emotional discrimination by F5 and F1. The results pointed out for the fact that, independently of the voice type, each emotion has is own specificity, visible in spectra, with a particular connection to a formant: Anger /F5, Sadness/ F4, Joy/F3. Further research needs to be considered on this last issue.